Mixed germ cell tumor of the testis in a young adult: A case repo (Indian Journal of Case Reports, 2026)
Testicular germ cell tumors (TGCTs) are the most common solid malignancy in young men aged 15–35 years, with mixed germ cell tumors posing particular diagnostic and staging challenges due to their combined seminomatous and non-seminomatous composition. We report a 22-year-old male who presented with a 4-month history of progressive right scrotal swelling. Imaging revealed bilateral common iliac and paraaortic lymphadenopathy. He underwent right radical orchidectomy. Histopathology confirmed a mixed seminomatous–non-seminomatous germ cell tumor (90% seminoma, 10% embryonal carcinoma) with lymphovascular invasion, staged as pT2 (AJCC 8th Edition). This case underscores the importance of complete pre-operative tumor marker assessment, including serum alpha-fetoprotein, meticulous histopathological sampling, and a multidisciplinary approach for optimal management.